Globalization and economic development essays in honour of J. George Waardenburg - Waardenburg, J. George; Storm, Servaas; Naastepad, C. W. M., 1961-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2001)
Globalization is widely regarded as a means not only of ensuring efficiency and growth, but also of achieving equity and development for those countries operating in the global economy. The book argues that this perception of globalization as the road to development has lost its lustre. The experience of the 1990s belied expectation of the gains, such as faster growth and reduced poverty, which could be achieved through closer integration in the world economy.
pt. 1. Globalization, instability and path dependence -- pt. 2. International capital flows -- pt. 3. Equity, employment and environment.
Includes bibliographical references and index.
Keywords: International economic relations; Globalization; Economic development; Electronic books